Delineation the effect of saline groundwater on the resistivity of middle part of Dammam Formation southwest of Samawah city, Southern Iraq - AL-Juboury, Abdullah A.; Thabit, Jassim M.; AL-Menshed, Firas H. (Iraqi Journal of Science, 2019)
The study area intendes for agricultural investment and establishment stations of water pumping for human use to the nearby areas, southwest of Samawah city. Twelve Two-Dimension (2-D) survey points were performed by using Wenner-Schlumberger array configuration to take the measurements. The inverse models of two survey point appear the effect of the saline groundwater that raises from Rus Formation, which caused a significant reduction in resistivity of the groundwater-bearing zone within middle Dammam Formation along the fault plane.